ANALISIS PENGARUH PENYERTAAN MODAL DAN LABA BUMD TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI JAWA TENGAH - Yahya, Carissa Marisa; Wildan Syafitri (Journal of Development Economic and Social Studies, 2024)
Central Java is a province in Indonesia that has the highest number of Regional-Owned Enterprises (BUMD), ideally can serve as an alternative source of revenue beyond taxes to increase the Original Regional Income (PAD). However, there are several challenges in the management of BUMD, particularly with the phenomenon of the COVID-19 pandemic having a significant impact on BUMD's revenue. The purpose of this research is to determine the effect of capital participation and BUMD profit on Original Regional Income (PAD) in the Districts/Cities of Central Java Province, using government investment theory and Regional-Owned Enterprises (BUMD) theory along with related regulations. The sample used is 35 Districts/Cities in Central Java province during the period 2018 to 2022. The research method used is panel data regression using Stata 14 software. This study used two control variables, Population and GDP Per Capita, with dummy variable COVID-19. The research finding that capital participation does not significant effect on original regional income, meanwhile BUMD profit has a significant positive effect on original regional income in the Districts/Cities of Central Java Province from 2018 to 2022.